Under the sea : archaeology and palaeolandscapes of the Continental Shelf - Bailey, G. N., 1948-; Harff, Jan; Sakellariou, Dimitris (Coastal research library ;, 2017)
This book focuses on issues of method and interpretation in studies of submerged landscapes, concentrating on illustrations and case studies from around Europe with additional examples from other parts of the world. Such landscapes were once exposed as dry land during the low sea levels that prevailed during the glacial periods that occupied most of the past million years and provided extensive new territories for human exploitation. Their study today involves underwater investigation, using techniques and strategies which are clearly set out in these chapters. The underwater landscape provides a rich source of information about the archaeology of human settlement and long-term changes in environment, climate and sea-level. This book highlights how such information can be revealed and interpreted. The examples presented here and the focus on techniques make this book of worldwide relevance. Chapters describe examples of underwater archaeological investigation as well as collaboration with offshore industries and legal, management and training issues relating to underwater cultural heritage. Such studies point to the significance of this drowned landscape, and readers are invited to consider its human impact in terms of past settlement and population dispersal through palaeolandscape reconstruction and interpretation in relation to broader themes in human prehistory. This volume is based on work from COST Action SPLASHCOS, a four-year multi-disciplinary and multi-national research program supported by COST (European Cooperation in Science and Technology) and has something to benefit all those with an interest in the sea floor of the continental shelf and the archaeological and social impact of sea-level change, including archaeologists, marine scientists, geographers, cultural-heritage managers, commercial and governmental organisations, policy makers and interested members of the public.